Effects of Virality: Culinary MSME Brand Orientation in Using Social Media Influencers - Sinar Dharmayana Putra; Erwin Erwin (Jurnal Mirai Management, 2023)
In this study, marketing techniques for MSMEs are examined, including the usage of influencers to support product brands. However, whether or not viral content is contentious, it will undoubtedly have an impact on MSMEs. The goal of this study was to ascertain the influence of virality, band orientation, and influencers on MSME product brands and how they affect these items. The results of this study indicate that the use of influencers as a marketing strategy can provide significant benefits for culinary MSMEs. Influencers can create virality that increases brand awareness, consumer perceptions regarding brand quality, brand preferences, and consumer purchase intentions. Therefore, culinary MSMEs can take advantage of the potential of influencers and virality as an effective way to increase their marketing success and business growth. This study uses a questionnaire as a research instrument with a Likert scale (5 scales). Respondents to this study were 115 culinary MSME actors who used social media in running their business. The findings of this study suggest that culinary MSMEs can profit significantly from using influencers as a marketing approach. Influencers can encourage virality, which raises consumer perceptions of brand quality, preferences for brands, and buy intentions. As a result, culinary MSMEs can effectively boost their marketing success and company growth by using the potential of influencers and virality. Keywords: Virality, MSME, Brand Orientation, Influencer